Disaster theory an interdisciplinary approach to concepts and causes - Etkin, David (Butterworth-Heinemann, 2016)
Disaster Theory: An Interdisciplinary Approach to Concepts and Causes offers the theoretical background needed to understand what disasters are and why they occur. Drawing on related disciplines, including sociology, risk theory, and seminal research on disasters and emergency management, Disaster Theory clearly lays out the conceptual framework of the emerging field of disaster studies. Tailored to the needs of advanced undergraduates and graduate students, this unique text also provides an ideal capstone for students who have already been introduced to the fundamentals of emergency management. Disaster Theory emphasizes the application of critical thinking in understanding disasters and their causes by synthesizing a wide range of information on theory and practice, including input from leading scholars in the field